The â€˜Otherâ€™ physical transformations in 'The Adventures of Tintin' TV series - Tungary, Octavia (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Describing a race through the verbal and visual description of physical appearance is often used to create binary opposition between â€˜Usâ€™ and â€˜Otherâ€™, so it does in The Adventures of Tintin comic books by HergÃ©. In The Adventures of Tintin TV series adaptation (1991-2) by StÃ©phane Bernasconi, â€˜Otherâ€™s verbal and visual physical depictions that are portrayed in the comic books undergo transformations that occur on non-White characters. These transformationsï¼changes, additions, and omissionsï¼ can be clearly seen in the Tintin TV series entitled The Blue Lotus, Cigars of the Pharaoh, and The Broken Ear that are adapted from the comic books of the same titles. The theory of adaptation by Linda Hutcheon and Orientalism by Edward Said are used to reveal and explain the adapterâ€™s strategies to make the skin colours, costume, and deformity moderation and negotiation in order that the TV series can be accepted by the audience around the world today.